Functionalized Metamaterials Enable Frequency and Polarization Agility in a Miniaturized Lightweight Antenna Package. (13th January 2016) - Scarborough, Clinton P.; Werner, Douglas H.; Wolfe, Douglas E.
Abstract : Electromagnetic metamaterials share a perceived disadvantage with miniature radio communication antennas: limited operating bandwidths. In conventional radio systems, tuning has been confined to the radio, requiring broadband antennas and materials. With the advent of software defined and digital radios, adding the antenna into the plethora of tunable radio subsystems can become a reasonable proposition, allowing miniaturized antennas with narrow instantaneous (channel) bandwidths to be tuned across entire communications bands, depending on the channel in use. Moreover, the antenna will provide an effective filtering stage before the signal reaches the radio. The tunable metamaterial presented herein enables an antenna showcasing this functionality and more. Dramatic size reductions are made possible by a tunable, lightweight, miniaturized metamaterial. Tuning the metamaterial and antenna in tandem provides a dynamic operating channel, with a tunable, nearly arbitrary polarization response as an added benefit. Finally, this antenna provides one of the first examples in the literature of a practical device improved by functionalized metamaterials, which has been tested on a real‐world platform. Abstract : A tunable metamaterial combined with a miniaturized tunable antenna is presented as a possible replacement for existing miniature radio antennas. Dramatic size reductions and novel multifunctional capabilities are achieved without degrading performance.